A gift from SLOVEnia to the world - Klopčič, Sonja (knjige, 2021)
Nature, with pandemics, increasing temperatures and frequent storms and floods, is firing clear warning shots. There is no more denying that the actions of individuals and organizations are in many cases harmful to the planet. %If we want to bequeath a planet with decent living conditions to our descendants, we need to drastically transform the economy. I believe that this can only be done by conscious leaders who, with their heart wide open, perceive the world as a unified whole. Leaders who see their role in the wider context and are aware that their decisions directly affect the quality of many people%s lives. Such perception goes far beyond the narrow understanding of responsibility as being connected only to the material resources of an organization. Conscious leaders are aware that they are also responsible for the emotional and spiritual development of their employees, who should be healthy, brimming with life, and see meaning in their work. Such leaders do not manage their organizations solely as business ventures, but also as platforms for fulfilling their mission and the mission of their employees, and thereby contribute to the welfare of the community. They know that their responsibility extends far beyond the limits of the organizations they manage.
Keywords: medkulturno sporazumevanje; Mednarodno sodelovanje; Medosebni odnosi; poslovno sodelovanje; Vodenje